Respuesta :
Answer:
x=-1 and y=-9
Step-by-step explanation:
So the equations are 7x-3y=20 and y=5x-4
the second equation gives you a value that you can substitute in for y
sub for y in the first equation:
7x-3(5x-4)=20
distribute the 3 to the values in the parenthesis
7x-15x+12=20
combine like terms
-8x+12=20
subtract 12 from both sides
-8x=8
divide both sides by -8
x=-1
Now that you have your x value you should sub it into one of the equations to get the y value, we will sub it into the first equation
7(-1)-3y=20
multiply
-7-3y=20
add 7 to both sides
-3y=27
divide both sides by -3
y=-9
Substitute the values in to check your work
7(-1)-3(-9)=20
-7+27=20
20=20
correct, now the other equation
(-9)=5(-1)-4
-9=-5-4
-9=-9
correct
Answer:
x = - 1, y = - 9
Step-by-step explanation:
Given the 2 equations
7x - 3y = 20 → (1)
y = 5x - 4 → (2)
Substitute y = 5x - 4 into (1)
7x - 3(5x - 4) = 20
7x - 15x + 12 = 20
- 8x + 12 = 20 ( subtract 12 from both sides )
- 8x = 8 ( divide both sides by - 8 )
x = - 1
Substitute x = - 1 into (2) for corresponding value of y
y = (5 × - 1) - 4 = - 5 - 4 = - 9
Solution is (- 1, - 9)